2022
DOI: 10.3390/ijms23010487
|View full text |Cite
|
Sign up to set email alerts
|

The QseEF Two-Component System-GlmY Small RNA Regulatory Pathway Controls Swarming in Uropathogenic Proteus mirabilis

Abstract: Bacterial sensing of environmental signals through the two-component system (TCS) plays a key role in modulating virulence. In the search for the host hormone-sensing TCS, we identified a conserved qseEGF locus following glmY, a small RNA (sRNA) gene in uropathogenic Proteus mirabilis. Genes of glmY-qseE-qseG-qseF constitute an operon, and QseF binding sites were found in the glmY promoter region. Deletion of glmY or qseF resulted in reduced swarming motility and swarming-related phenotypes relative to the wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Another recent paper has also highlighted the role played by the QseEF TCS in modulating swarming motility. In general, the activated sensor kinase QseE determines the phosphorylation of the regulator QseF that, in turn, activates the expression of GlmY together with CheA and RcsB, two antagonist regulators of flagellum production [ 245 ]. A recent case report has described evidence of acquisition of resistance to imipenem and amikacin in a Proteus mirabilis clinical isolate, not previously showing this feature.…”
Section: Two-component Systemsmentioning
confidence: 99%
“…Another recent paper has also highlighted the role played by the QseEF TCS in modulating swarming motility. In general, the activated sensor kinase QseE determines the phosphorylation of the regulator QseF that, in turn, activates the expression of GlmY together with CheA and RcsB, two antagonist regulators of flagellum production [ 245 ]. A recent case report has described evidence of acquisition of resistance to imipenem and amikacin in a Proteus mirabilis clinical isolate, not previously showing this feature.…”
Section: Two-component Systemsmentioning
confidence: 99%
“…Meanwhile, the most recent study revealed that the QseEF twocomponent system-GlmY Small RNA (sRNA) regulatory pathway controls the P. mirabilis swarming. This is the first report in which a pathway mediated by a two-component system through an sRNA was disclosed to be involved in swarming migration (Lin et al, 2022). This observation is intrigue given the fact that in silico study reported the detection of 14 sRNA candidates, conserved in the orthologous regions of P. mirabilis, which biological role remains unexplained (KishanRaj et al, 2018).…”
Section: Swarming Motilitymentioning
confidence: 88%
“…In this Special Issue, a total of 18 excellent and interesting papers [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], consisting of 13 original research studies [3][4][5][6][10][11][12][14][15][16][18][19][20], as well as five reviews, are published [7][8][9]13,17]. They cover many subjects of transcriptional regulation, including studies on cis-regulatory elements, transcription factors (TF), chromatin regulators, and ncRNAs.…”
mentioning
confidence: 99%
“…Generally, bacteria utilize the two-component system (TCS) method, such as QseEF, to control gene expression in response to rapid environmental changes. Of note, many recognized mechanisms function through the post-transcriptional control of small non-coding RNAs (sRNAs), and their identification is rapidly increasing in number and variety in the context of bacteria regulatory functions [19]. Interestingly, in a study in the present Special Issue, the authors identified the QseEF homologue of Proteus mirabilis, an Important pathogen of the urinary tract, principally in patients with indwelling urinary catheters, and they found it is involved in the modulation of swarming motility through the sRNA GlmY.…”
mentioning
confidence: 99%
See 1 more Smart Citation